The - ida Wahyuni (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2022)
Background: The era of the COVID-19 pandemic has triggered education for a learning innovation to keep it running safely, effectively and efficiently. Student practical learning needs to be facilitated by the existence of a virtual laboratory. The virtual electronic patient medical record laboratory is an integration of e-learning systems and health information systems. This system is a recommendation for independent practicum activities for health students, especially medical records and health information. The research objective is to design an electronic laboratory medical record system to increase access to independent learning. Subjects and Methods: The research design is an action research conducted at Poltekkes Tasikmalaya with stages of diagnosis, planning, action and evaluation system. The evaluation was carried out to see the level of usability of the system for users, namely students of medical records and health information. 54 respondents who filled out the online usability questionnaire using the total usability scale (SUS) method. Results: the electronic patient record laboratory system was successfully built up to the mockup design stage. This system is acceptable and feasible to be used as a recommendation for a virtual laboratory practice model for students. The usability score obtained 58 which means the marginal low and “ok” of adjective rating to use. Conclusions: the system gets a marginal usability rating of low and ok to use. System design to be more attractive and the interaction between features that need to be developed. It is recommended that this system be developed for mobile-based applications so that it can make it easier and increase motivation for practical learning for students independently. Keywords: Laboratory, Virtual, Electronic, Patient, Record, SUS